Energy Management in Hybrid Renewable Energy-Based EV Charging Systems Using PID Controller - Mr. Shaik Akbar Basha,; Mr. Pandiyan V,; Mr. P.R. Rajeev,; Mr. M. Seenivasan, (Utilitas Mathematica, 2024)
This paper presents an innovative energy management system (EMS) for electric vehicle charging stations (EVCS) that integrates hybrid renewable energy sources, including fuel cells, wind, and solar. The proposed system employs a Proportional-Integral-Derivative (PID) controller to overcome the limitations of traditional artificial neural network (ANN) controllers, ensuring better stability, accuracy, and cost-effectiveness. A 40kW EVCS model is developed in MATLAB Simulink to demonstrate the optimization of power generation, EV power demand, and charging times. The results show significant reductions in charging costs and greenhouse gas emissions, making the system both environmentally and economically sustainable.